Myriad of Health Care Financing Reforms in Zambia: Have the Poor Benefited? - Bona Mukosha Chitah; Collins Chansa; Oliver Kaonga; Netsanet Walelign Workie (Taylor & Francis Group, 2018)
Zambia has implemented a number of financing and organizational reforms since the 1990s aimed at increasing efficiency, enhancing equity, and improving health outcomes. This study reviews the distributional impact of these health reforms on enhancing equity at the regional level and for different socioeconomic groups. Data from three nationally representative household surveys were collected, and a benefit incidence analysis was conducted to determine the distributional impact over the period 2010-2015. The results show that distribution of subsidies and utilization of outpatient services at public health facilities in Zambia has consistently been in favor of urban provinces. Further, distribution of health subsidies across the ten provinces in Zambia does not correspond to reported illnesses in each province. The study also shows that utilization of outpatient services at public (hospitals and health centers) and private health facilities is generally in favor of the rich, and utilization of both inpatient and outpatient services at public and private health facilities benefits the rich more than the poor. And although the results show a pro-poor redistribution of benefits across income groups in 2015 compared to 2010 whereby the poorest two income groups received more than a 20% share of benefits in each quintile, the benefits were still lower than their health needs. This is contrary to the richest two income groups whose share of benefits was higher than their health needs in both 2010 and 2015. The study concludes that Zambia has not yet fully attained its long-term health reform vision of "equity of access to quality health care" despite years of successive health reforms. The study calls for the Zambian government to complement strategies on financial risk protection with deliberate supply- and demand-side actions in order to enhance equity. Improvements in long- and short-term planning and regular monitoring and evaluation are critical.